The Effect of E-Service Quality and E-Trust on E-Loyalty of BNI Mobile Banking Users with E-Customer Satisfaction as an Intervening Variable - Ni Putu Eka Wulandari Wulandari; Gusti Ngurah Joko Adinegara; Yeyen Komalasari; Christimulia Purnama Trimurti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid development of digital banking services, particularly mobile banking, has become a crucial factor influencing customer satisfaction and loyalty. This study aims to analyze the effect of E-Service Quality and E-Trust on E-Loyalty of BNI Mobile Banking users, with E-Customer Satisfaction as the intervening variable. The research seeks to determine the extent to which service quality and user trust can enhance customer satisfaction and loyalty in using mobile banking services. The data used in this study are primary data obtained through questionnaires distributed to 97 respondents who are BNI Mobile Banking users in Denpasar City. The research applies a quantitative approach using Partial Least Square (PLS) analysis to examine both direct and indirect relationships among variables. The findings indicate that E-Service Quality has a significant positive effect on both E-Customer Satisfaction and E-Loyalty. Similarly, E-Trust significantly and positively influences E-Customer Satisfaction and E-Loyalty. Furthermore, E-Customer Satisfaction is proven to play an intervening role that strengthens the relationship between E-Service Quality and E-Trust with E-Loyalty. These results suggest that higher digital service quality and greater user trust lead to increased satisfaction, which ultimately fosters stronger loyalty among BNI Mobile Banking users. Based on these findings, it is recommended that banks continuously improve their digital service quality and build stronger customer trust to maintain satisfaction and sustain loyalty amidst the increasingly competitive digital banking industry.